In-cell Solid-State NMR Studies of Antimicrobial Peptides - Separovic, Frances; Keizer, David W.; Sani, Marc-Antoine (Frontiers in Medical Technology, 2020)
Antimicrobial peptides (AMPs) have attracted attention as alternatives to classic antibiotics due to their expected limited pressure on bacterial resistance mechanisms. Yet, their modes of action, in particular in vivo, remain to be elucidated. In situ atomistic-scale details of complex biomolecular assemblies is a challenging requirement for deciphering the complex modes of action of AMPs. The large diversity of molecules that modulate complex interactions limits the resolution achievable using imaging methodology. Herein, the latest advances in in-cell solid-state NMR (ssNMR) are discussed, which demonstrate the power of this non-invasive technique to provide atomic details of molecular structure and dynamics. Practical requirements for investigations of intact bacteria are discussed. An overview of recent in situ NMR investigations of the architecture and metabolism of bacteria and the effect of AMPs on various bacterial structures is presented. In-cell ssNMR revealed that the studied AMPs have a disruptive action on the molecular packing of bacterial membranes and DNA. Despite the limited number of studies, in-cell ssNMR is emerging as a powerful technique to monitor in situ the interplay between bacteria and AMPs.